Knockdown of FcγRIII in an arthritic temporomandibular joint reduced the nociceptive response - Kramer, Phillip R. (2010)
FcγRIII (CD16) is a receptor expressed on immune cells that selectively binds immmunoglobulin G (IgG) molecules, IgG binding results in cellular activation and cytokine release. IgG is an important factor in arthritis and can be found in arthritic temporomandibular joints (TMJ). We hypothesize that a reduction in FcγRIII expression in the TMJ tissues will reduce the nociceptive and inflammatory response in an inflamed joint. To test this hypothesis siRNA, either naked or complexed with linear polyethylenimine (PEI) was injected into the superior joint space of the TMJ. After administration of siRNA the joint was injected with saline or with complete Freund’s adjuvant (CFA) to induce arthritis. Nociceptive responses were quantitated in the rat by measuring the animal’s meal duration. FcγRIII expression in the TMJ tissue was assayed by immunocytochemistry or western. Cleavage of FcγRIII transcript was then assayed by 5′ rapid amplification of cDNA ends method (5′ RACE). Interleukin-1β (IL-1β) and IgG content was measured in the TMJ tissue by ELISA. The results indicate that injection of FcγRIII siRNA reduced the amount of FcγRIII in the TMJ tissues and that the transcript was cleaved in a manner consistent with a RNA interference mechanism. Moreover, injection of FcγRIII siRNA reduced the nociceptive response of rats with an arthritic TMJ and reduced the amount of pro-inflammatory cytokine IL-1β. We conclude that FcγRIII contributes to the pain resulting from inflammatory arthritis of the TMJ and that siRNA has the potential to be an effective treatment for this disorder.